China’s Emancipatory Diplomacy for a Peaceful, Democratic, and Sustainable Global Community - Jelica Stefanović-Stambuk; Slobodan Popović (The Review of International Affairs)
This research explores the theoretical formation of the People’s Republic of China’s diplomacy. Despite efforts to relate its theorisation into communicable terms, the West considers them a thin veneer for the ruling Communist Party’s propaganda. China’s diplomatic actions are portrayed as manipulations of a power-greedy state for global might, ready to tear apart the existing arrangements and overtake the United States on the apex of world power. Although a “wolfwarrior” stream in diplomatic practice can sometimes run high, studying China’s theorisation of diplomacy reveals the ideational normativity of willpower for relationships of mutuality. Xi Jinping’s “Thought on Major Country Diplomacy”, formatively shaped in 2014, shows that China’s diplomacy emancipatory crux is frightening to those alarmed by the country’s might. We will test this proposition by conducting a contextual content analysis of relevant sources. The Chinese emancipatory diplomacy conceives the use of the state power for the joint sharing of life, time, and the planet. It is poised to lead to the principled and just consent of all states to achieving an inclusive, equitable, fair, democratic, and peaceful international order of balanced and just autonomous development and global governance through mutually ascertained multilateralism in a human community with a shared future.